NETWORK OF EDUCATIONAL INSTITUTIONS FOR TRAINING BACHELOR OF LAW AND COMPLIANCE OF ACHIEVEMENTS OF SCIENTIFIC AND EDUCATIONAL STAFF WITH LICENSING CONDITIONS - Cherneha, Vitalii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: formation of a vision for a network of educational institutions for training lawyers at the bachelor’s level and compliance of the achievements of scientific and pedagogical workers with licensing conditions. Research methods: analysis, synthesis, induction, deduction (thoroughly applied according to the chosen research subject); system-structural method (contributed to the disclosure of a network of educational institutions for training lawyers at the bachelor’s level); modeling (applied to form conclusions and recommendations on the subject of the selected research). Results: it was concluded that currently the training of a new generation of lawyers at the bachelor’s level is carried out by an extensive network of higher education institutions of various forms of ownership, subordinate to the National Academy of Sciences of Ukraine, the Ministries of Internal Affairs of Ukraine, Education and Science of Ukraine, Finance of Ukraine, Justice of Ukraine, city and regional councils, the Security Service of Ukraine, the Administration of the State Border Guard Service of Ukraine, the State Statistics Service of Ukraine, the State Emergency Service of Ukraine, UKOOPOSVITA, and Ukrkoopspilka. Scientifically substantiated proposals are proposed aimed at improving the regulatory and legal requirements for the compliance of the achievements of scientific and pedagogical workers with licensing conditions. Discussion: the modern network of educational institutions of Ukraine for training lawyers at the bachelor’s level is presented. The names of educational and professional programs of the bachelor’s level in the specialty "Law" are highlighted, which are studied in higher education institutions of Kyiv, Vinnytsia, Dnipro, Zhytomyr, Zaporizhia, Ivano-Frankivsk, Kropyvnytskyi, Lutsk, Lviv, Mykolaiv, Odesa, Poltava, Rivne, Sumy, Ternopil, Kharkiv, Kherson, Khmelnytskyi, Cherkasy, Chernivtsi, Chernihiv, as well as Vinnytsia, Dnipropetrovsk, Donetsk, Zaporizhia, Kyiv, Lviv, Odessa, Poltava, Rivne, Khmelnytskyi regions. Some of the regulatory and legal requirements on the compliance of the achievements of scientific and pedagogical workers with the licensing conditions for conducting educational activities are discussed.